The Antiproliferative Effects Of Moringa Oleifera Leaf Extracts And Silver Nanoparticles On Human Leukemia Kasumi-1 Cells - Khor, Kang Zi (2020)
Moringa oleifera, also commonly known as ‘moringa’, is widely cultivated in tropical and subtropical regions across the globe. All parts of the moringa tree can be utilised and extensive studies have shown that various parts of the moringa tree exhibit anti-cancer properties. This study determined the effects of sequential moringa leaf extracts and silver nanoparticles synthesised from moringa leaf extract on Kasumi-1 leukemia cells. Dried moringa leaf powder was sequentially extracted with the assistance of ultrasound starting with absolute ethanol, followed by 50% ethanol, and finally, deionised water. The aqueous extract was incorporated to synthesise silver nanoparticles, whereby the optimum conditions to generate moringa silver nanoparticles (MO-AgNPs) were eight hours of incubation at 60 °C with 1 mM silver nitrate and 1% moringa aqueous extract from sequential extraction. The three various extracts and MO-AgNPs were used to treat Kasumi-1 cells for 24, 48, and 72 hours with concentrations ranging between 400 and 12.5 μg/mL, while cell viability was determined with 3(4, 5-dimethythiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. The experimental outcomes revealed that after 72 hours of treatment, the moringa leaf ethanolic extract displayed the strongest inhibitory effects on Kasumi-1 cells with IC50 of 10 μg/mL, in comparison to moringa leaf 50% ethanolic extract (25 μg/mL) and aqueous extract (>400 μg/mL). Interestingly MO-AgNPs exhibited the strongest cytotoxic effects on Kasumi-1 cells with an IC50 of 7.5 μg/mL.